Chloronychia: The goldman-fox syndrome - Implications for patients and healthcare workers - Robert A Schwartz; Nicole Reynoso-Vasquez; Rajendra Kapila (Wolters Kluwer Medknow Publications, 2020)
Nail coloration has many causes and may reflect systemic disease. White nails (leukonychia) are common; rubronychia is rare, whereas green (chloronychia) is occasionally evident. Chloronychia, the Fox-Goldman syndrome, is caused by infection of an often damaged nail plate by Pseudomonas aeruginosa. P. aeruginosa is an opportunistic pathogen known for localized and systemic infections. It can spread cryptically in a variety of ways, whether from an infected nail to a wound either autologously or to a patient as a surgical site infection, and many represent a threat to elderly, neonatal, or immunocompromised patients who are at increased risk of disseminated pseudomonas infection. We will review the Goldman-Fox syndrome as an occupational disorder of homemakers, nurses, plumbers, and others often with wet hands. At a time when hand washing is being stressed, especially in healthcare settings, examination of nails should be emphasized too, recalling the possibility of surgical site infection even with a properly washed and gloved medical care provider. Pseudomonasmay be a community-acquired infection or a hospital or medical care setting-acquired one, a difference with therapeutic implications. Since healthcare workers represent a threat of nosocomial infections, possible guidelines are suggested.